The amino-terminal domain of the androgen receptor co-opts extracellular signal-regulated kinase (ERK) docking sites in ELK1 protein to induce sustained gene activation that supports prostate cancer cell growth - Rosati, Rayna; Patki, Mugdha; Chari, Venkatesh; Dakshnamurthy, Selvakumar; McFall, Thomas; Saxton, Janice; Kidder, Benjamin L.; Shaw, Peter E.; Ratnam, Manohar (American Society for Biochemistry and Molecular Biology, 2016)
The ETS domain transcription factor ELK1 is in a repressive association with growth genes and is transiently activated through phosphorylation by ERK1/2. In prostate cancer (PCa) cells the androgen receptor (AR) is recruited by ELK1, via its amino-terminal domain (A/B), as a transcriptional co-activator, without ELK1 hyper-phosphorylation. Here we elucidate the structural basis of the interaction of AR with ELK1. The ELK1 polypeptide motifs required for co-activation by AR versus those required for activation of ELK1 by ERK were systematically mapped using a mammalian two-hybrid system and confirmed using a co-immunoprecipitation assay. The mapping precisely identified the two ERK-docking sites in ELK1, the D-box and the DEF (docking site for ERK, FXFP) motif, as the essential motifs for its cooperation with AR(A/B) or WTAR. In contrast, the transactivation domain in ELK1 was only required for activation by ERK. ELK1-mediated transcriptional activity of AR(A/B) was optimal in the absence of ELK1 binding partners, ERK1/2 and serum-response factor. Purified ELK1 and AR bound with a dissociation constant of 1.9 × 10−8 m. A purified mutant ELK1 in which the D-box and DEF motifs were disrupted did not bind AR. An ELK1 mutant with deletion of the D-box region had a dominant-negative effect on androgen-dependent growth of PCa cells that were insensitive to MEK inhibition. This novel mechanism in which a nuclear receptor impinges on a signaling pathway by co-opting protein kinase docking sites to constitutively activate growth genes could enable rational design of a new class of targeted drug interventions.